THE ANGLO-OTTOMAN TRADE IN THE WESTERN CASPIAN REGION IN THE 16TH CENTURY - Urdakal, Osman (History, Archeology and Ethnography of the Caucasus, 2024)
This article analyzes the engagement between Ottoman authorities and English merchants from the Muscovy Company within the Caucasus during the latter half of the sixteenth century. This period constitutes a significant phase in the evolution of international commerce and diplomatic ties, coinciding with the peak of the Ottoman Empire’s political and economic influence and the concomitant emergence of England as an active participant in global politics and trade. In 1553, Sultan Suleiman the Magnificent bestowed a capitulation of commercial privileges upon the English merchant and explorer Anthony Jenkinson, marking the inception of formal relations between the two states in the realm of trade. Of particular significance in the development of these relations were the occurrences of 1579–1580, during which English merchants affiliated with the Muscovy Company commenced vigorous commercial operations within the Western Caspian region. Here they interacted with the Ottoman Pasha Osman Özdemiroğlu, who at that time held a key role in consolidating Ottoman influence within the Caucasus. It is noteworthy that, contrary to prevailing assumptions, the genesis of these contacts did not transpire in the Mediterranean, but rather within the Caucasus. Consequently, the Caucasus emerged as the locus of the initial establishment of direct commercial linkages between Ottoman authorities and English merchants. Subsequently, this interaction served as a crucial phase in the evolution of official inter-state commercial relations, a trajectory that continued within the purview of the Levant Company, founded on September 11, 1581. The article underscores the significance of employing general historical and comparative historical analysis as the primary research methodologies. Particular emphasis is placed upon the utilization of archival sources preserved within Turkey, many of which previously remained beyond the purview of scholarly investigation. For the first time in Russian, the text of the Ottoman-English treaty of 1580 is published, constituting a substantial contribution to scholarly dissemination and facilitating a more profound comprehension of the incipient stages of trade and diplomatic ties between the Ottoman Empire and England.